2022
DOI: 10.3389/fspor.2022.1035190
|View full text |Cite
|
Sign up to set email alerts
|

Inter-set stretch: A potential time-efficient strategy for enhancing skeletal muscle adaptations

Abstract: Time is considered a primary barrier to exercise adherence. Therefore, developing time-efficient resistance training (RT) strategies that optimize muscular adaptations is of primary interest to practitioners. A novel approach to the problem involves combining intensive stretch protocols with RT. Conceivably, integrating stretch into the inter-set period may provide an added stimulus for muscle growth without increasing session duration. Mechanistically, stretch can regulate anabolic signaling via both active a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 66 publications
0
9
0
Order By: Relevance
“…Most recently, Warneke et al ( 2023a , b , c ) suggested static stretching as a potential alternative to common resistance-training methods, as the authors were not able to obtain significant differences in strength adaptations, muscle hypertrophy and flexibility when comparing 1 h of daily stretching with a commonly performed hypertrophy training routine (5 × 12 repetitions, three times per week). As resistance training can also improve ROM to a similar extent as static stretching (Alizadeh et al 2023 ), the practical applicability and additional benefit of 1 h stretching per muscle group must considered critically (Schoenfeld et al 2022 ). Furthermore, stretch training evidence is limited to studies mostly addressing lower extremity muscles (Warneke et al 2023b ).…”
Section: Introductionmentioning
confidence: 99%
“…Most recently, Warneke et al ( 2023a , b , c ) suggested static stretching as a potential alternative to common resistance-training methods, as the authors were not able to obtain significant differences in strength adaptations, muscle hypertrophy and flexibility when comparing 1 h of daily stretching with a commonly performed hypertrophy training routine (5 × 12 repetitions, three times per week). As resistance training can also improve ROM to a similar extent as static stretching (Alizadeh et al 2023 ), the practical applicability and additional benefit of 1 h stretching per muscle group must considered critically (Schoenfeld et al 2022 ). Furthermore, stretch training evidence is limited to studies mostly addressing lower extremity muscles (Warneke et al 2023b ).…”
Section: Introductionmentioning
confidence: 99%
“…This study was performed to counteract methodological limitations described by Schoenfeld et al [ 22 ] and others [ 5 , 6 , 14 ], indicating that long stretching durations were impractical. While increasing strength may potentially be particularly relevant for sport-specific tasks such as jumping and sprinting [ 46 ], or ball throwing velocity in handball [ 47 ], a recently published systematic review did not find stretch-induced performance enhancement [ 48 ], which seems in accordance with the lack of results for the rate of force development and explosive strength parameters obtained in the current study [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…Wohlann et al [ 17 ] pointed out that 15 min of supervised stretching has the potential to substitute high-intensity pectoralis resistance training. However, Schoenfeld et al [ 22 ] highlighted the impracticality of stretching-induced strength gains, especially when this type of training requires a second person or special equipment. Therefore, this study explores the possibility of alternative and more practical stretching training such as home-based stretching training and directly compares it to supervised stretching training.…”
Section: Introductionmentioning
confidence: 99%
“…The reason for using inter-set foam rolling lies in the fact that some individuals in the gym often stretch the agonist muscle between sets. Although inter-set stretching is scientifically investigated for its theoretical advantage in terms of muscular hypertrophy as a chronic adaptation [ 31 , 32 , 33 , 34 ], the acute effects are not well-investigated and appear to be detrimental for resistance training performance in the set subsequent to the stretching procedure [ 35 , 36 ]. On the other hand, the literature reports that pre-exercise foam rolling enhances the range of motion without compromising muscle strength [ 9 , 10 ], but it seems to negatively affect the subsequent performance when it is performed between sets in lower limbs exercise [ 19 , 20 ].…”
Section: Discussionmentioning
confidence: 99%